Investor Factors - BETERMIER, SEBASTIEN; CALVET, LAURENT E.; KNÜPFER, SAMULI; KVAERNER, JENS SOERLIE (Journal of Finance, 2025)
ABSTRACT This paper develops an empirical methodology for extracting pricing factors from investor portfolio data. We apply this approach to the stockholdings of Norwegian individual investors from 1997 to 2017. A two‐factor model, featuring the market portfolio and a long‐short portfolio constructed from the holdings of investors sorted by age or wealth, explains both the common variation in portfolio holdings and the cross section of stock returns. Portfolio tilts toward the long‐short investor factor correlate with indebtedness, macroeconomic exposure, gender, and investment experience. Our paper illustrates the benefits of using holdings data for explaining the risk premia of financial assets.